Martha and Hilary and the stranger - Steel, Danielle; Rogers, Jacqueline (New York, N.Y. : Delacorte Press, 1991)
Hilary learns an important lesson in safety: never accept a ride from a stranger.
Keywords: Strangers -- Juvenile fiction; Accidents -- Prevention -- Juvenile fiction